Apolipoproteins, lipids and risk of cancer. Issue 11 (8th February 2016) - Borgquist, Signe; Butt, Talha; Almgren, Peter; Shiffman, Dov; Stocks, Tanja; Orho‐Melander, Marju; Manjer, Jonas; Melander, Olle
Abstract : The epidemiological evidence for an obesity‐cancer association is solid, whereas the association between obesity‐associated lipoprotein levels and cancer is less evident. We investigated circulating levels of Apolipoprotein A1 (ApoA1), Apolipoprotein B (ApoB), LDL‐cholesterol (LDL‐C) and HDL‐cholesterol (HDL‐C) and association to risk of overall cancer and common cancer forms. The Malmö Diet and Cancer Study, a population‐based prospective cohort study, enrolled 17, 035 women and 11, 063 men (1991–1996). Incident cancer cases were ascertained by record linkage with the Swedish Cancer Registry until end of follow‐up, January 1, 2012. Baseline serum levels of ApoA1 and ApoB were analyzed for the entire cohort and HDL‐C and LDL‐C levels in 5, 281 participants. Hazard ratios, with 95% confidence interval, were calculated using Cox's proportional hazards analysis. In the entire cohort, none of the exposures were related to overall cancer risk (HRadj ApoA1 = 0.98, 95%CI: 0.95, 1.01; HRadj ApoB = 1.01, 95%CI: 0.98–1.04). Among men, ApoB was positively associated with cancer risk (HRadj ApoB = 1.06, 95%CI: 1.01, 1.10). Female breast cancer risk was inversely associated with ApoB (HRadj = 0.92, 95%CI: 0.86, 0.99). Among both genders, ApoA1 was inversely associated with lung cancer risk (HRadj = 0.88, 95%CI: 0.80, 0.97), whereas high ApoB increased lung cancer risk (HRadj = 1.08, 95%CI: 0.99, 1.18). Colorectal cancer risk was increased with high ApoB (HRadj = 1.08, 95%CI: 1.01, 1.16) among both genders. Apolipoprotein levels were not associated with prostate cancer incidence. Circulating levels of apolipoproteins are associated with overall cancer risk in men and across both genders with breast, lung and colorectal cancer risk. Validation of these findings may facilitate future primary prevention strategies for cancer. Abstract : What's new? Obesity and cancer are associated, although the underlying biological mechanisms are not fully understood. In this population‐based study of 28, 098 individuals, incidences of overall cancer and breast, lung and colorectal cancers were found to be associated with circulating levels of apolipoproteins A1 and B (ApoB). The nature of the associations varied. Whereas ApoB was positively linked to cancer risk in men, it was inversely associated with breast cancer risk in women. Meanwhile, no association was found for prostate cancer incidence. The findings may improve the understanding of the obesity‐cancer association and help facilitate primary preventive strategies.